Mineralogia de sedimentos ricos em fósforo e cobre - Tonello, Maurício Sonda (2019)
The agate stone exploratory activity can cause profound changes in soil and landscapes. The characterization of the soil in the landscape near the mining can serve as a scientific base and contributed for regeneration strategies in these areas after the end of exploitation. In this study, using a new methodology, we aimed to evaluate the different land uses in the nearest lands of mining and the impact on soil quality, using satellite images together with the evaluation of chemical and physical properties of soil. The landscape native forest represented the largest occupation of adjacent territory (600 meters of radius) agate exploration, reaching 35%. The second largest occupation of the territory studied was the grassland with 32%, followed by crops with 29%. Together, these landscapes occupy 96% of the study area, covering 1830.78 hectares in different agate mines agate inventoried by the environmental agency of the state of Rio Grande do Sul. The analysis of soil chemical properties in the mines suggest loss of quality when exposed the exploitation of precious stones. Among the attributes, the decrease in soil base saturation and organic matter content in addition to the increase in aluminum levels were the most affected. It can be inferred, that the soil nearest the mines can serve as indicators for the reconstruction of fertility of degraded soils exploitation with mines once they do not suffer impact over his soils by the exploitation. The methodology applied in that study will complements strategies to recover degraded soils by opencast mining.